The show : - Lazenby, Roland (McGraw-Hill, 2006)
The L.A. Lakers have long been one of the NBA's most exciting teams. In The Show, critically acclaimed sportswriter Roland Lazenby brings the story of this charismatic team to life in an unprecedented oral history, featuring such legendary players as Wilt Chamberlain, Jerry West, Kareem Abdul- Jabbar, and Magic Johnson, along with current stars like Shaquille O'Neal and Kobe Bryant. Through in-depth interviews with players, coaches, and many other key figures, Lazenby follows the Lakers from their birthplace in 1946 Minneapolis to their eventual successes and failures in Los Angeles, using his flair for storytelling and eye for detail to show you exactly why the 14-time NBA champion Lakers are a celebrated favorite for sports fans all over America.